Essential economics for business - Sloman, John; Jones, Elizabeth (2020)
"Welcome to the sixth edition of Essentials Economics for Business. If you are a student on a business or management degree or diploma course and taking a module which includes economics, then this book is written for you. Such modules may go under the title of Business Environment or Business Context, or they may simply be called Introduction to Economics or Introduction to Business Economics. Alternatively, you may be studying on an MBA and need a grounding in basic economic concepts and how they apply to the business environment"--
Keywords: Managerial economics; Economics; Business; Industrial management